Upaya Meningkatkan Karakter Siswa dalan Pelajaran Sejarah Kebudayaan Islam Melalui Metode Role Playing peserta didik Kelas 4 di SD Negeri 1 Podoluhur - Mungawanah, Fiatul; Mursilatussa’adah, Mursilatussa’adah (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
Islamic Cultural History is a sub-material in PAI. SKI teaching and learning activities should not only be limited to the transfer of knowledge but also transfer educational value or value education. The image of SKI subjects among students is synonymous with stories. Learning carried out with lectures makes students feel bored. Therefore, researchers are interested in researching learning methods that are able to produce good learning outcomes. The objectives of this study are to improve the character of students through SKI learning. This research is a qualitative research that uses an ethnographic approach. The subjects of this study are principals, teachers, and grade 4 students at SD Negeri 1 Podoluhur. The results of this study prove that the application of the role playing method improves character as one of the learning outcomes of students in SKI learning. It is evidenced by the increase in the presentation of student learning outcomes by 10% per cycle with the accumulation of student activity from 55% to 95% and the accumulation of student understanding from 50% to 95%. In addition, it also improves the character of religious, nationalist, independent and mutual cooperation with students. The conclusion of the study using the role playing method is very effective in improving character through student learning outcomes.